Bioactivity of A Bacillus Thuringiensis Cry1AC Toxin to Spodoptera litura - Y. Andi Trisyono; Serafina T.S. Rahayu; St. Margino (Universitas Gadjah Mada, 2004)
The transgenic cotton expressing Bacillus thuringiensis toxin Cry1Ac in Indonesia has been planted since 2000 for controlling Helicoverpa armigera. Spodoptera litura is another lepidopteran insect that also attacks cotton. The objective of this research was to determine the toxicity of Cry1Ac to S. litura. The acute toxicity was determined using neonates of S. litura exposed to artificial diets treated with series concentrations of Cry1Ac ranging from 0.14 to 625 mg/ml, and larval mortality was recorded at the seventh day after treatment. The chronic toxicity was determined by exposing neonate to artificial diets treated with the sublethal concentrations (LC5 and LC40). The growth and development of treated larvae were compared with those of the control farvae. Cry1Ac was toxic to neonate with LC5 values of 71.9, 18.1, 24.7, and 16.2 mg/ml for S. litura collected from Wonosari, Bantul-l, Bantul-2, and Kopeng, respectively. Cry1Ac was more toxic than formulated B. thuringiensis (LC50 = 724.8 mg/ml). Larvae exposed continuously to artificial diets treated with sublethal concentrations of Cry1Ac (0.61 and 9.77 mg/ml) showed no significant difference on weight and length of each life stages than those of the control larvae. These indicate that the application of the tested sublethal concentrations of Cry I Ac did not affect the growth and development of S. litura. However, increasing concentrations of Cry1Ac (156.25 and 625 mg/ml) significantly reduced the weight of surviving larvae. These findings suggest that application of Cry1Ac to S. litura shows some toxicological effects. The effectiveness of the transgenic cotton in controlling S. litura in field situation will be discussed.